Investigation of the Protective and / or Therapeutic Effects of Lycopene on Diethylnitrosamine-Induced Chronic Hepatotoxicity Using Biochemical, Molecular and Histopathological Data - Kaya, Emre; Yılmaz, Seval; Çeribaşı, Ali Osman; Telo, Selda (Van Yüzüncü Yıl Üniversitesi, 2020)
The aim of the study is to investigate the role of lycopene on diethylnitrosamine (DEN)-induced chronic hepatotoxicity using biochemical, molecular and histopathological approaches. Thirty five male Wistar albino rats were assigned into five groups of 7 rats each. Groups were formed as control, lycopene, DEN, lycopene+DEN and DEN+lycopene. Lycopene was applied to rats every other day at 10 mg/kg/bw, gavage for 10 days. DEN was applied intraperitoneally to rats at a single dose, 200 mg/kg/bw for 90 days. Lycopene administration was started 10 days before the DEN administration in lycopene+DEN group, together with the DEN administration in DEN+lycopene group. The study was terminated 90 days after DEN administration. DEN caused the oxidative stress by the increased malondialdehyde level and the decreased reduced glutathione level, antioxidant enzyme activities (p<0.001). Lycopene administration improved the biochemical indices of both blood and liver tissue compared to the DEN group. RT-PCR analysis revealed that the catalase enzyme in the DEN group increased expression levels. Histopathologically, many histopathologic changes such as karyomegaly, necrosis and hydropic degeneration were observed in the liver tissues of the DEN and lycopene+DEN groups. Both biochemical and histopathological results showed that healing of DEN+lycopene group was better than lycopene+DEN group. These results suggest that besides the protective effects, the therapeutic effect of lycopene is due to its antioxidant effects on DEN?induced hepatotoxicity.

Çalışmanın amacı, likopenin dietilnitrozamin (DEN) kaynaklı kronik hepatotoksisite üzerindeki rolünü biyokimyasal, moleküler ve histopatolojik yaklaşımları kullanarak araştırmaktır. 35 adet erkek Wistar albino rat, her grupta 7 rat olacak şekilde 5 gruba ayrılmıştır. Gruplar, kontrol, likopen, DEN, likopen+DEN ve DEN+likopen şeklinde oluşturulmuştur. Likopen, gün aşırı olarak 10 mg/kg/vücut ağırlığı dozunda gavaj yoluyla 10 gün uygulanmıştır. DEN, ratlara 200 mg/kg vücut ağırlığı dozunda intraperitoneal olarak tek doz 90 gün uygulanmıştır. Likopen uygulaması, likopen+DEN grubunda DEN uygulamasından 10 gün önce, DEN+likopen grubunda ise DEN uygulaması ile birlikte başlamıştır. DEN uygulamasından 90 gün süre sonra çalışma sonlandırılmıştır. DEN, dokularda malondialdehid düzeylerinde artışa, redükte glutatyon düzeyi ve antioksidan enzim aktivitelerinde düşüşe sebep olarak oksidatif strese neden olmuştur (p<0,001). Likopen uygulaması hem kan hem de karaciğer dokusunda DEN grubuna kıyasla biyokimyasal endekslerde iyileşme sağlamıştır. RT-PCR analizlerinde DEN grubundaki katalaz enziminin ekspresyon düzeylerini arttırdığı belirlenmiştir. Histopatolojik olarak, DEN ve likopen+DEN gruplarının karaciğer dokularında karyomegali, nekroz ve hidropik dejenerasyon gibi birçok histopatolojik değişiklikler gözlenmiştir. Hem biyokimyasal hem de histopatolojik sonuçlarda DEN+likopen grubundaki iyileşmesinin likopen+DEN grubundan daha iyi olduğu gözlenmiştir. Bu sonuçlar, likopenin koruyucu etkisinden ziyade tedavi edici etkisinin DEN’e bağlı hepatotoksisitede likopenin antioksidan etkisine bağlı kaynaklandığını göstermektedir.
Biyokimyasal, Moleküler ve Histopatolojik Veriler Kullanılarak Likopenin Dietilnitrozamine Bağlı Kronik Hepatotoksisite Üzerine Koruyucu ve / veya Tedavi Edici Etkilerinin Araştırılması
Keywords: Veterinary Surgery; Veteriner Cerrahi